EFL Learner’s Beliefs in Pronunciation Learning - Sarjaniah Zur; Abdul Halim; Nur Dianti Syafwa (IAIN KENDARI, 2021)
This qualitative study aims to identify students’ response to learners’ beliefs about pronunciation skill. The participants of this study consist of 35 students from the students of Pronunciation class in an institution, class A and B in the second semester of the academic year of 2019/2020. The qualitative data were analyzed by questionnaire. This study focuses on students’ beliefs in learning pronunciation. The result shows that students have four beliefs in learning pronunciation that is beliefs on learning process, learning pronunciation, strategy used in learning pronunciation, and the solution and importance of pronunciation. This will provide information to lecturers and universities to take advantage of beliefs in learning pronunciation.Keywords: importance of pronunciation; learning pronunciation; students’ beliefs